Pola Budaya Politik Masyarakat Pendatang: Studi Pada Orang Palembang di Kota Pangkalpinang - Dewantara, Muhammad (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The pattern of political culture is the pattern of people's behavior in the life of the state, nation, state administration, government politics, and the law carried out by the whole community every day. One of these political cultures is influenced by immigrant communities living in one area. This study aims to determine the cultural patterns of the immigrant community, especially the Palembang people in Pangkalpinang City, which are cognitive, affective, and evaluative oriented. Knowing the immigrant community's cultural way in Pangkalpinang City will produce conclusions and prove that the immigrant community (Palembang people) carries out the pattern of political culture in Pangkalpinang City.